HLA-G genetic polymorphism in 57 Portuguese white families studied by PCR-RFLP and PCR-SSOP - Alvarez, M. (1999)
http://www.sciencedirect.com/science/article/B6VJ0-3Y868K9-T/1/709af60970490b64a33bbeda3e3b35ca